2010
DOI: 10.1007/s10120-010-0544-5
|View full text |Cite
|
Sign up to set email alerts
|

A Western single-center experience with endoscopic submucosal dissection for early gastrointestinal cancers

Abstract: Patients and Methods PatientsTwenty-fi ve unselected consecutive patients (10 men and 15 women; mean age, 70 years; range, 47-88 years) with EGICs underwent ESD at our institution from April 2007 to September 2009. There were 3 esophageal, 7 gastric, 1 duodenal, and 14 colonic lesions (Table 1). The mean size of the lesions was 25 mm (range, 10-50 mm). Inclusion criteria followed those of Oyama [9] for lesions of the esophagus; the extended Gotoda criteria for the stomach [10]; and laterally spreading tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…However, Sakamoto et al [22] and Ohata et al [23] showed that 30 ESD treatments performed independently in the colon were sufficient to obtain an acceptable R0 resection rate, procedure duration, and complication rate. This learning curve was confirmed by studies showing that during the first 25 treatments, the perforation rates were 12-28% [24][25][26][27]. In a European study, Probst et al [15] observed a considerable improvement in resection parameters after two endoscopists each performed 25 procedures as the procedure time decreased from about 200 to 136 min and the proportion of R0 resections increased from 48 to 84.5%.…”
Section: Discussionmentioning
confidence: 66%
“…However, Sakamoto et al [22] and Ohata et al [23] showed that 30 ESD treatments performed independently in the colon were sufficient to obtain an acceptable R0 resection rate, procedure duration, and complication rate. This learning curve was confirmed by studies showing that during the first 25 treatments, the perforation rates were 12-28% [24][25][26][27]. In a European study, Probst et al [15] observed a considerable improvement in resection parameters after two endoscopists each performed 25 procedures as the procedure time decreased from about 200 to 136 min and the proportion of R0 resections increased from 48 to 84.5%.…”
Section: Discussionmentioning
confidence: 66%
“…[3][4][5] A few small series also were reported from Western countries. [6][7][8][9][10][11] However, ESD has not yet been standardized, and it is technically difficult, time consuming, and potentially hazardous. 7 The aim of this study was to evaluate the efficacy and safety of ESD by use of a new water jet-assisted ESD (WESD) system in patients with early gastric neoplastic lesions.…”
mentioning
confidence: 99%
“…It should be emphasized that the successful treatment of this case can be at least partially attributed to the increased confidence and expertise in the management of acute perforations as a result of the advanced training on endoscopic submucosal dissection recently pursued by one of the authors (S.C.) at one of the most experienced Japanese institutions. 10 Because of the lack of large prospective trials, the efficacy of clipping and the role of contamination, for large as well as for small timely repaired perforations, remain to be further determined. Provided that the complication is promptly recognized and that the edges of the tear are clean and easily approachable, clipping should be considered as a safe and useful technique to attempt to obliterate even large iatrogenic esophageal perforations.…”
Section: Discussionmentioning
confidence: 99%